Anomalous solidification behaviour in rapidly cooled Ti–Nb–Ta ternary alloys - Theo Mossop; David J. Browne; Mert Celikin (Journal of Materials Research and Technology)
Processing β-titanium alloys via metal additive manufacturing (AM) is a rapidly expanding area, hence understanding their solidification behaviour under rapid cooling is critical. The solidification of Ti–Nb–Ta alloys was investigated under various cooling rates (c. 2000-20,000 K/s) using suction casting. An inverted partitioning effect was determined for Ti–20Nb–10Ta (wt.%) alloy, where solute is preferentially retained in the dendrites under very rapid solidification. In relatively slower-cooled samples, the microsegregation followed Scheil solidification theory. Moreover, columnar morphology was replaced with equiaxed structures with increasing cooling rate. These effects were not observed in the thermodynamically similar binary alloys, Ti–25Nb and Ti–35Ta.